Details of the dome atop the Mandapa (pillared hall) of the Bhandasar Temple - Temples of India Project Team (Jio Institute, 2024)
Details of the dome, which is atop the mandapa (pillared hall) of the Bhandasar Temple. The central large dome is complemented by four small domes on small diagonal sides and the mukhamandapa (front porch) of the temple has an individual dome. The base of the main domes has windows on all sides, and the side domes have painted ornamented bands.